2010
DOI: 10.1292/jvms.09-0273
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospira spp. in Clinically Healthy Racing Horses in Korea

Abstract: ABSTRACT. Leptospirosis is a zoonotic disease of global importance, and has a worldwide distribution. The present study aimed to determine leptospiral seroprevalence in clinically healthy racing horses from all three racecourses in Korea. Serum samples from 1,226 racing horses were examined using a microscopic agglutination test to detect the presence of antibodies against 18 Leptospira serovars. Of the tested samples, 307 (25.0%) were found to be positive. The distribution of seroprevalence differed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 15 publications
4
30
0
3
Order By: Relevance
“…In Sweden, ponies and coldbloods had a lower odds ratio of seropositivity to serovar Icterohaemorrhagiae infection compared with other breeds (Baverud et al 2009). This is also in agreement with the findings from Korea where a low seroprevalence was found in Thoroughbred horses used for racing due to high level of management and care associated with this breed (Jung et al 2010). In this study, the high seroprevalence of serovar Bratislava was found among Nooitgedacht horses (66.67%).…”
Section: Demographic Factorssupporting
confidence: 92%
See 3 more Smart Citations
“…In Sweden, ponies and coldbloods had a lower odds ratio of seropositivity to serovar Icterohaemorrhagiae infection compared with other breeds (Baverud et al 2009). This is also in agreement with the findings from Korea where a low seroprevalence was found in Thoroughbred horses used for racing due to high level of management and care associated with this breed (Jung et al 2010). In this study, the high seroprevalence of serovar Bratislava was found among Nooitgedacht horses (66.67%).…”
Section: Demographic Factorssupporting
confidence: 92%
“…Another study in Korea has shown this seasonal variation where more antibodies against Leptospira serovars were detected in summer and autumn compared to spring and winter (Jung et al 2010).…”
Section: Risk Factorsmentioning
confidence: 82%
See 2 more Smart Citations
“…5), indicating that other factors or indirect links must be involved. Still, regional differences in prevalence may be partly related to climatic conditions as leptospires excreted by infected animals can remain infectious for long periods of time in humid climates (Jung et al, 2010), whereas they have less chance of propagating the infection in drier areas.…”
Section: Discussionmentioning
confidence: 99%